STYLISTIC METHODS OF INFLUENCE IN KOREAN NEWSPAPER DISCOURSE (Academicia Globe: Inderscience Research, 2024)
This article is devoted to the impact of stylistic techniques on the readership of an electronic newspaper in Korean. The articles of the Korean electronic newspaper "News" are the material for practical analysis. The article examines stylistic figures-anaphores, antitheses and rhetorical questions, which are most often used in the texts of newspaper articles on general political topics. Stylistic figures play a special role in this process, which perform both expressive and excretory, as well as organizational and textual functions. These figures ensure the information accuracy of the text, highlight the integrity of semantic fragments and, thus, contribute to the perception of the text in accordance with the author's intentions. Contact-type anaphores are especially prone to the realization of an expressive function. An equally important role is played by a new figure, in particular, the combination of anaphora with antithesis and syntactic parallelism. The use of stylistic figures in the expressive function in the media mainly serves intentional criminals and depends on the individual style of the author of the newspaper article.